GANGGUAN KOGNITIF PADA PASIEN GAGAL JANTUNG KONGESTIF DAN FAKTORFAKTOR YANG MEMPENGARUHINYA - Hendro Birowo*, Diatri Nari Lastri*, Lukman H Makmun**, Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION COGNITIVE IMPAIRMENT ARE FOUND MORE COMMON IN CONGESTIVE HEART FAILURE PATIENTS COMPARE TO NORMAL POPULATION DECLINE IN COGNITIVE FUNCTION CAN SIGNIFICANTLY REDUCE PATIENTS QUALITY OF LIFE AND INCREASE BOTH MORBIDTY AND MORTALITY